An investigation and analysis of safety issues in Polish small construction plants - Dąbrowski, Andrzej (International journal of occupational safety and ergonomics, 2015)
The construction industry is a booming sector of the Polish economy; however, it is stigmatised by a lower classification due to high occupational risks and an unsatisfactory state of occupational safety. Safety on construction sites is compromised by small construction firms which dominate the market and have high accident rates. This article presents the results of studies (using a checklist) conducted in small Polish construction companies in terms of selected aspects of safety, such as co-operation with the general contractor, occupational health and safety documents, occupational risk assessment, organization of work, protective gear and general work equipment. The mentioned studies and analyses provided the grounds to establish the main directions of preventive measures decreasing occupational risk in small construction companies, e.g., an increase in engagement of investors and general contractors, improvement of occupational health and safety (OSH) documents, an increase in efficiency of construction site managers, better stability of employment and removal of opposing objectives between economic strategy and work safety.